Paclitaxel‐Coated Balloons in Refractory Nonanastomostic Airway Stenosis Following Lung Transplantation. Issue 10 (23rd July 2014) - Greer, M.; Fuehner, T.; Warnecke, G.; Noack, H.; Heilmann, T.; Haverich, A.; Welte, T.; Gottlieb, J.
<x xml:space="preserve">Abstract</x> Airway stenosis represents the commonest airway complication following lung transplantation, affecting between 7% and 18% of patients. Existing treatment options offer limited efficacy and can cause additional patient morbidity. Paclitaxel‐coated balloons (PCB) have proved effective in managing postinterventional coronary artery re‐stenosis. In a first‐in‐man study, we evaluated similar PCBs in refractory nonanastomotic airway stenosis in 12 patients. Following a single application, luminal patency was maintained in 50% at 270 days. No significant peri‐interventional or early postinterventional complications occurred. Given these encouraging initial findings, further studies appear warranted.